Investing in adult nutrition to reduce mobility problems in ageing population - Ray Wagiu Basrowi; Levina Chandra Koe; Tonny Sundjaya (World Nutrition Journal, 2021)
As people age, most body organs deteriorate. Osteoporosis, arthritis, sarcopenia, muscle aches, low back pain and neuropathy are common mobility issues in the elderly. Body mass index (BMI), physical inactivity, and having comorbidities increase the likelihood to have mobility health problems. One in every ten adults over the age of 45 years in Indonesia develops these mobility problems, and one in every fifteen adults has difficulty in walking/stepping before entering the elderly age. Nutrition has been reported to have important role in controlling weight and physical locomotive organs. Generally, 46% adults in Indonesia have vitamin A deficiency, 70% vitamin C deficiency, 77% vitamin E deficiency, and inadequate calcium intake. Low nutrition intake can result in increasing mobility problems that lead to health issues in the aging population. Dietary strategies are necessary to achieve healthy ageing. Currently, no standardized guideline has been developed for preventing mobility health problems in Indonesia. This calls for urgent need to hinder poor quality of life in elderly population.